Implementation of High Speed Self Switching Frequency Agile RADAR - K Jansi Lakshmi; K Surya Narayana Reddy (Institute of Advanced Engineering and Science, 2014)
The radar has to resist diversified jamming; High Speed self-adaptive frequency agility is an important and effective function for radars to resist jamming. The procedure to achieve this function are described, and the function is realized with FPGA using Hardware description Language, the validity is proved by on- line sampling and simulation. The High speed self-adaptive frequency agility module can analyze the type of jamming to select transmitting frequency to avoid the frequencies which have interference, under frequency diversity and fixed frequency, respectively. The general application on a searching radar shows that the module has good real-time and anti- jamming capacity.